Maternal dietary choices might impact intrauterine healing processes and postnatal phenotype and function in human fetuses with spina bifida aperta - early clinical observations and implications from a retrospective cohort study - Kohl, Thomas (Biomedicines, 2025)
Background: The severity of postnatal symptoms in patients with spina bifida aperta (SBA) is also determined by secondary factors that damage the exposed neural tissue throughout gestation. The purpose of this report is to present clinical cases, from 2010 to 2025, and a new hypothesis for a nonsurgical means of prenatal secondary prophylaxis. Patients: Eight fetuses underwent minimally invasive fetoscopic patch closure of SBA. After delivery, an unusual degree of prenatal patch healing was observed. Furthermore, time to complete postnatal skin closure was shorter (mean ± SD: 22.00 ± 6.53 days) than in 31 contemporary patients without dietary restrictions (Mean ± SD: 44.35 ± 11.91 days; p < 0.001). Four of the eight prenatally operated women reported that they ate plant-based food most of the time but also some meat throughout gestation; the other four were strict vegetarians. Two other fetuses with SBA at the level of the second and third lumbar vertebrae, respectively, had not undergone prenatal surgery. Following delivery, they presented with a markedly preserved surface of the neural cord and exhibited L5 motor function. One mother of the postnatally operated patients was on a vegetarian diet; the other one on a vegan diet. Conclusions: These early clinical observations point to the possibility that maternal plant-based diets might ameliorate the loss of neurological function and facilitate wound healing in human fetuses with SBA. If this impact of maternal dietary habits holds true, it opens the door to a far-reaching, easily available, non-invasive secondary prophylaxis in prenatally operated and unoperated fetuses with SBA and some other malformations.